Clinical Education for the Health Professions Theory and Practice - Nestel, Debra; Reedy, Gabriel; McKenna, Lisa; Gough, Suzanne (Springer Nature Singapore : Imprint: Springer, 2023)
128 illus., 75 illus. in color. eReference.